2010
DOI: 10.1017/s1049023x00007834
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Medical Command and Control Using Performance Indicators in a Full-Scale, Major Aircraft Accident Exercise

Abstract: Introduction: Large, functional, disaster exercises are expensive to plan and execute, and often are difficult to evaluate objectively. Command and control in disaster medicine organizations can benefit from objective results from disaster exercises to identify areas that must be improved. Objective: The objective of this pilot study was to examine if it is possible to use performance indicators for documentation and evaluation of medical command and control in a full-scale major incident exercise at two level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 10 publications
4
38
0
Order By: Relevance
“…The measurable performance indicators extracted from this process have been used for many years in Swedish disaster management training. In addition, the same indicators have been used in an international study and as an evaluation tool in full-scale exercises [18-21]. …”
Section: Introductionmentioning
confidence: 99%
“…The measurable performance indicators extracted from this process have been used for many years in Swedish disaster management training. In addition, the same indicators have been used in an international study and as an evaluation tool in full-scale exercises [18-21]. …”
Section: Introductionmentioning
confidence: 99%
“…It has also been used in the European Journal of Trauma and Emergency Surgery 43 44 and mentioned in an editorial in the same journal 45. Two of the templates31 34 39 are routinely used for reporting from exercises. Data on medical management during a mass casualty incident exercise31 are normally used to assess the healthcare system in a mass casualty incident simulation and exercise.…”
Section: Resultsmentioning
confidence: 99%
“…An online registry for the healthcare system is designed using this instrument. Performance indicators for major incident medical management34 39 have also been used in additional publications 17 46–50. For the three publications lacking author email,23 36 38 we were unable to attain information on whether they have been used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have found positive effects from training using simulation methods on various aspects of EMS work, such as team processes, management, patient safety, mass casualty triage, clinical performance, self-efficacy, and more (Brannan et al, 2008;Daniels & Auguste, 2013;Okuda & Bryson, 2009;Pattillo, 2006;Salas, Gregory, & King, 2011;Weaver et al, 2014). Full-scale exercises with a high degree of fidelity are often considered the best approach to teaching medical management (D. Cohen et al, 2013;Gryth et al, 2010). However, there has been criticism of high fidelity training -such as the naïve realism claimsand much of medical management training is performed using low-fidelity simulations (Bewley & O'Neil, 2013;Legemaate, Burkle Jr., & Bierens, 2012;Lennquist, 2005;Sundnes & Birnbaum, 2003).…”
Section: Use Of Simulationsmentioning
confidence: 99%